Dinâmica econômica, infraestrutura e logística no Matopiba - Caroline Nascimento Pereira; César Nunes de Castro; Gabriela Lanza Porcionato (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The agricultural frontier known as Matopiba, has shown considerable growth in recent years. This dynamism results from the agricultural production of grains such as soybean, corn and cotton in large properties and with use of machinery and equipment. Thus, the work measures aspects of the economic dynamics of the region, with the characterization of agricultural, industrial and service activities and mapping the infrastructure and logistics. It was observed that even with strong growth, the region still has bottlenecks to be overcome to facilitate the storage and flow of production, such as ports, highways and railroads. In addition, it suffers from social inequality, which demands public policies to balance the best use of resources and the fair distribution of income. Thus, it is possible to affirm that it is an enclave region of difficult coalition due to the different forces existing in the region, such as business agriculture, preservation areas, family agriculture, quilombolas and indigenous.
Keywords: Q1; R1; R11; 330; Matopiba; economics development; infrastructure; logistics